Randomness of encryption keys generated by super H-antimagic total labeling - Antonius Cahya Prihandoko; Yudha Alif Auliya; Diksy Media Firmansyah; S Slamin (Indonesian Combinatorial Society (InaCombS), 2020)
SuperH-antimagic total labeling (SHATL) can be utilized to generate encryption keys. The keys are then used to establish the improved block and stream ciphers. In these ciphers, different blocks were encrypted by the different keys, but all block keys were connected one another. These conditions make the developed cryptosystems more secure and require less keys storage capacity compared to the ordinary block and stream cipher. The randomness of the generated keys, however, still need to be tested. The test is necessary to ensure that there is no specific pattern that can be utilized by any intruder to guess the keys. This paper presents the randomness tests applied to all key sequences generated by both the improved block scheme and the stream based scheme.